Overview of Online Shopping Behavior in Emerging Adulthood Ages 18-25 Years in Kupang City - Dopong, Musdalifa; Lerik, Mariana Dinah Ch; Damayanti, Yeni (Universitas Nusa Cendana, 2023)
Online shopping is a transaction process carried out through media or intermediaries in the form of online buying and selling sites or social networks that provide goods or services that are traded. This study aims to determine the description of online shopping behavior in emerging adulthood aged 18-25 years in Kupang City. The approach used is a quantitative approach with a descriptive research type. The sample in this study amounted to 381 students in Kupang City aged 18-25 years. The sampling technique used was probability sampling with the method of proportionate stratified random sampling. The results of the study found that the data obtained through categorization and the odd ratio found that male students were more likely to do online shopping behavior of 0,24 times compared to women, while based on the age of thw students who 22-25 years old and over tend to do online shopping behavior by 2,37 times compared to students aged 18-21 years.